Clinical and Demographic Features of Children Diagnosed with Cystic Fibrosis after Sweat Test Screening for Failure to Thrive, Chronic Diarrhea or Recurrent Pulmonary Infections - Çapan Konca; Ali Güneş; Velat Şen; Servet Yel; İlyas Yolbaş; Aydın Ece; Mehmet Fuat Gürkan (Güncel Pediatri)
Introduction: The aim of this study was to investigate the incidence of cystic fibrosis (CF) in patients with recurrent pulmonary infection, chronic diarrhea and failure to thrive having no specific diagnosis and also to investigate the demographic features, and clinic and laboratory findings of such patients. Materials and Methods: The diagnosis of CF has been established through measuring the sweat conductivity in children presenting with one or more characteristic phenotypic features of CF. A chloride concentration lower than 59 mmol/l was interpreted as negative; 60-79 as borderline and over 80 as positive. A borderline sweat test result supported with genetic mutation, nasal potential difference or elastase activity was diagnosed as atypical CF. Results: A total of 356 patients fulfilled the study criteria. Twenty (5.6%) patients were diagnosed as CF. The mean age of the patients was 19.3±18.1 months and 234 (65.7%) of them were boys. Of the patients suffered from recurrent pulmonary infection, chronic diarrhea and failure to thrive; 15.5%, 10.1%, and 7% were diagnosed as CF, respectively. Major presenting complaints were fever, respiratory tract diseases, failure to thrive, and chronic diarrhea in patients with CF. A total of 430 sweat tests were applied to 356 patients and 20 of the 33 patients with a test resulting over 60 mmol/L were diagnosed as CF. Conclusions: CF should be considered for the differential diagnosis of the patients presented with chronic diarrhea, recurrent pulmonary infection, and failure to thrive. While the incidence of CF in white people is approximately 1 in 3000 individuals, we found a higher rate of 5.6% in our study group. (Journal of Current Pediatrics 2013; 11: 96-101)